Analysis Of The Performance Of Junior High Schools In The Nisam Sub-District Using The Data Envelopment Analysis Method - Mudawali, Mudawali; Abdulllah, Dahlan; Sahputra, Ilham (Malikussaleh University, Aceh, Indonesia, 2025)
Education plays a major role in improving the quality of human resources. To support this effort, an application is needed so that it can measure the efficiency of education performance quickly and automatically. This research uses the Data Envelopment Analysis (DEA) method. The Data Envelopment Analysis method is a method that utilizes linear programming to compare decision-making units, by comparing one Decision Making Unit (DMU) with other DMUs that use similar resources to produce similar outputs. This research successfully developed an application to measure the performance efficiency of junior high schools in Nisam District. The application was designed using UML, PHP, and MySQL, and data was collected through interviews with school officials. The application provides an attractive user interface and can calculate linear programming with the DEA method, in accordance with calculations using Lindo 6.1 software. The data used for the efficiency analysis includes input data, such as the number of teachers, other students, facilities and infrastructure, the number of students admitted in 2023, certified and uncertified teachers, teachers with master's degrees, PPPK teachers, honorarium teachers, as well as the average student pass rate and the number of students graduating in 2023 as output. Of the 6 sample schools, 5 schools (83.33%) achieved efficiency, while 1 school (16.66%) was not efficient.